FORMULASI KEBIJAKAN PENDIRIAN LEMBAGA PERADILAN KHUSUS HUBUNGAN INDUSTRIAL DI KABUPATEN BEKASI - Waluyo Zulfikar; Ipah Ema Jumiati (Jurnal Administrasi Publik, 2017)
This research was conducted with the aim of creating a series of policies to overcome the problems of industrial relations disputes that often occur in Bekasi Regency. Bekasi Regency is a district whose revenue is supported by the existence of the industry. Bekasi Regency is the largest industrial area in Indonesia, this is causing the more complex characteristics of society in Bekasi Regency. With the increasing industrial sector in Bekasi Regency, this has an impact on the high problem of industrial relations disputes in Bekasi regency. This is indicated by the continuous increase of disputes between workers and employers every year in the jurisdiction of industrial relations of Bekasi Regency. This research uses descriptive analysis with qualitative approach, it is intended to be able to arrange a right policy concept to overcome the problems of industrial relations that often occur in Bekasi Regency.